Investigating the Staff Agility and the Role of Empowerment in their Improvement - Mohammad Mostafa Dahmardeh (Journal of Global Pharma Technology, 2017)
Staff ability is not used efficiently in most organizations and managers are not able to get their potential capacities. The aim of this study is to investigate the role of the staff agility and the role of empowerment in their improvement. The study is practical according to purpose and is descriptive survey based on the method of gathering data. To collect theoretical foundations and history in this study, the library studies, articles and academic journals have been used. Also field research and search in statistical population were used to collect statistical information to test research hypotheses. A psychological empowerment questionnaire (Spreitzer) and organizational agility (Zhang and Sharifi) have been used to collect information in this study. The statistical population consists of all the employees of the Social Security Organization in Zabol. The sample size was selected using Morgan table. SPSS software was used for data analysis. Descriptive tests of frequency, mean and standard deviation are used for demographic variables and key variables and also inferential tests such as Pearson correlation, and stepwise linear regression and Friedman test have been used to rank the components of psychological empowerment. Data results indicate that there is a significant relationship between the components of psychological empowerment and staff organizational agility.Keywords: organizational agility, Psychological empowerment, Social security organization, Staff, Organization